PKM Pencegahan Stunting Melalui Pemberdayaan Ekonomi Keluarga - Mashita, Juni; Anggresta, Vella; Maya, Siska (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
High population growth causes problems, one of which is stunting. Stunting is a nutritional problem for children under five years old (toddlers). The impact of stunting is not only on individuals but also on countries. The impact of stunting on individuals includes increased health costs, cognitive decline, decreased achievement, learning capacity and work capacity, which ultimately has an impact on the country's development. Furthermore, the impact of stunting can also be short term or long term. Short-term impacts include children's vulnerability to infection and less than optimal cognitive development. Meanwhile, the long-term impact is more about increasing the risk in adulthood of chronic diseases such as diabetes or cardiovascular disease. One activity program that can prevent stunting is by carrying out family economic empowerment activities. Family economic problems then become one of the triggers for limited food availability in the household, decreased quality of care and feeding for children, to unhealthy home environmental conditions and lack of access to health services. So with an approach to empowering the family economy, it starts with arranging a leadership pattern to be able to manage finances well. In this community service program, the lecturer team was given the opportunity by partners to help socialize about this problem to be conveyed to the students' parents at Ra Baitul Muslimin. The solution offered in this service is to explain the importance of preventing stunting in children through a family economic empowerment approach, where a mother as a family member has the opportunity to earn more income. So that with economic independence, mothers will have the opportunity to upgrade their knowledge of nutrition, additional income, adequate education and health.